Consumer Buying Behavior of Toothpaste In District Kurukshetra: A Study on Consumer Behavior and Preferences in Purchasing Toothpaste in District Kurukshetra (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Consumer is king’-the statement carries profound truth init. Today the success of any firm depends upon the satisfaction of consumers.For satisfying the consumers the firm should know about the behavior of theconsumers. In these circumstances understanding consumer is very difficult taskbecause of the changing technology, innovation, and changes in life style. Itis difficult to classify consumers by conventional demographic factors andunless their thought process and buying behavior are fully understood decisionson product designs and packaging, branding and distribution channels are likelyto be misplaced. This study mainly focus on understanding the externalfactors like demographic, social, cultural, price, quality product attributesetc. for buying toothpaste. The market share of any product is highlydetermined by the purchasing behavior on the consumers. Following study isconducted by me to find out the behavior of the consumers, to analyze thepreference of consumers and consumer awareness. Descriptive research design wasadopted and the data is collected through primary and secondary sources. Themethods adopted for conducting survey is questionnaire. Simple random samplingtechnique was adopted for selecting the consumers.